2022
DOI: 10.1186/s12967-022-03584-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined lifestyle, mental health, and mortality in US cancer survivors: a national cohort study

Abstract: Background Adopting healthy lifestyles and staying mentally health are two cost-effective modifiable strategies that cancer survivors can implement in self-management. We aimed to evaluate the independent, mediation, interaction, and joint associations of combined lifestyle and mental health with mortality in cancer survivors. Methods We performed a cohort study including 3145 cancer survivors from National Health and Nutrition Examination Survey (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
(102 reference statements)
2
8
0
Order By: Relevance
“…These findings hold clinical significance because previous studies have reported a possible association between fibromyalgia and cancer 13 . However, the awareness of being at increased risk of developing cancer may exacerbate the anxiety of fibromyalgia patients, hampering disease management 30,31 . To some extent, our results also support that there is no inevitable relationship between cancer and fibromyalgia.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These findings hold clinical significance because previous studies have reported a possible association between fibromyalgia and cancer 13 . However, the awareness of being at increased risk of developing cancer may exacerbate the anxiety of fibromyalgia patients, hampering disease management 30,31 . To some extent, our results also support that there is no inevitable relationship between cancer and fibromyalgia.…”
Section: Discussionsupporting
confidence: 80%
“…13 However, the awareness of being at increased risk of developing cancer may exacerbate the anxiety of fibromyalgia patients, hampering disease management. 30,31 To some extent, our results also support that there is no inevitable relationship between cancer and fibromyalgia. However, the limitations in our study require further investigation in subsequent articles.…”
Section: Interpretation Of Findingssupporting
confidence: 75%
“…A study from the Guangzhou Cancer Registry (GCR) 10 found the benefit of adopting a healthy lifestyle for the extension of life expectancy and the prevention of premature death among cancer survivors in China. A previous study in the United States also showed that cancer survivors with a higher healthy lifestyle score (3–5) had a substantially lower risk of all‐cause and non‐cancer mortality 37 . Besides, a prospective study that enrolled 1425 newly diagnosed stages I–III colorectal cancer survivors found having a lifestyle highly in line with the WCRF/AICR recommendations was associated with a decreased all‐cause mortality risk 38 .…”
Section: Discussionmentioning
confidence: 93%
“…A previous study in the United States also showed that cancer survivors with a higher healthy lifestyle score (3-5) had a substantially lower risk of all-cause and noncancer mortality. 37 Besides, a prospective study that enrolled 1425 newly diagnosed stages I-III colorectal cancer survivors found having a lifestyle highly in line with the WCRF/AICR recommendations was associated with a decreased all-cause mortality risk. 38 However, there were also limitations in these studies, which restricted the generalizability of their findings.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, patients with anhedonia may be less inclined to change their lifestyle and take part in healthy behaviours such as physical activities (Leventhal, 2012) or perceive the benefits when doing so. This in turn may impact the changes of survival when confronted with cancer (Liu et al, 2022; Vijayvergia & Denlinger, 2015).…”
Section: Discussionmentioning
confidence: 99%